Plasma Membrane Transporters in Modern Liver Pharmacology - Jose J. G. Marin (Scientifica)
The liver plays a crucial role in the detoxification of drugs used in the treatment of many diseases. The liver itself is the target for drugs aimed to modify its function or to treat infections and tumours affecting this organ. Both detoxification and pharmacological processes occurring in the liver require the uptake of the drug by hepatic cells and, in some cases, the elimination into bile. These steps have been classified as detoxification phase 0 and phase III, respectively. Since most drugs cannot cross the plasma membrane by simple diffusion, the involvement of transporters is mandatory. Several members of the superfamilies of solute carriers (SLC) and ATP-binding cassette (ABC) proteins, with a minor participation of other families of transporters, account for the uptake and efflux, respectively, of endobiotic and xenobiotic compounds across the basolateral and apical membranes of hepatocytes and cholangiocytes. These transporters are also involved in the sensitivity and refractoriness to the pharmacological treatment of liver tumours. An additional interesting aspect of the role of plasma membrane transporters in liver pharmacology regards the promiscuity of many of these carriers, which accounts for a variety of drug-drug, endogenous substances-drug and food components-drug interactions with clinical relevance.